Anything goes [videorecording (DVD)] - Porter, Cole, 1891-1964 (Trafalgar Releasing, 2023)
When the S.S. American heads out to sea, etiquette and convention head out the portholes as two unlikely pairs set off on the course to true love - proving that sometimes destiny needs a little help from a crew of singing sailors, a comical disguise, and some good old-fashioned blackmail.